Iman Kepada Malaikat dan Rasul-Rasul Allah Serta Kewajiban Mentaati Rasulullah SAW - Firdaus, Firdaus; Andita, Lidya; Ainurrochimah, Saras; Andiyah, Tati Yalina; Wismanto, Wismanto (STAI Denpasar Bali, 2024)
Faith in angels and Allah's messengers is an important part of the pillars of faith that form the basis of the beliefs and behaviors of Muslims. In modern life full of ethical and social challenges, the understanding of faith in angels and apostles, as well as the obligation to obey the Prophet PBUH, has become very relevant to affirm moral and spiritual values. This research aims to explore the importance of this belief in building the character of Muslims and how this teaching can be a solution to today's challenges. The method used in this study is a qualitative approach with an analytical descriptive method. Data was collected through literature studies and literature analysis from a variety of relevant sources, including tafsir books, books, and academic journals. The results of the study show that faith in angels and apostles has a significant influence in shaping ethical awareness, responsibility, and behavior in accordance with Islamic teachings. Obedience to the Prophet PBUH also strengthens important human values in community life, such as justice, compassion, and unity. In conclusion, faith in angels and apostles and obedience to the Prophet PBUH not only strengthens the spiritual aspect, but also plays an important role in building a life of noble character and balance between the relationship with Allah and fellow humans.